2019
DOI: 10.3390/polym11121969
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Aluminum 2-Carboxyethyl-Phenyl-Phosphinate and Its Flame-Retardant Application in Polyester

Abstract: A flame retardant aluminum 2-carboxyethyl-phenyl-phosphinate (CPA-Al) was synthesized through the salification reaction. The molecular structure of CPA-Al and thermal stability were characterized by solid nuclear magnetic resonance, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Subsequently, CPA-Al mixed in polyurethane was coated on polyester textile to obtain flame-retardant samples. The addition of 14.7 wt.% CPA-Al in textile sample can bring a limited oxygen index (LOI) value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…With the addition of g-C 3 N 4 , the quality of char residue improved slightly with many holes, which was attributed to the pyrolytic decomposition of g-C 3 N 4 . g-C 3 N 4 /PAZn-EP displayed a continuous and density char, indicated that it had good catalytic performance for char residues, which could provide a barrier to protect matrix, exhibiting excellent flame retardant and smoke suppression behavior [35]. The results are consistent with the CCT results.…”
Section: Char Residue Analysissupporting
confidence: 81%
“…With the addition of g-C 3 N 4 , the quality of char residue improved slightly with many holes, which was attributed to the pyrolytic decomposition of g-C 3 N 4 . g-C 3 N 4 /PAZn-EP displayed a continuous and density char, indicated that it had good catalytic performance for char residues, which could provide a barrier to protect matrix, exhibiting excellent flame retardant and smoke suppression behavior [35]. The results are consistent with the CCT results.…”
Section: Char Residue Analysissupporting
confidence: 81%
“…75 PHRR shows an intense decline with increasing content of ES-CaCO 3 nanofiller. Based on a previous report on the mechanism of PHRR, 76,77 the noticeably reduced PHRR here indicates increased of inhibition of firing, and reduction of the burning intensity. Thus, a better charring and barrier effect, retarding of combustion, a reduction of volatile smoke, and termination of the free radical chain reaction in the gaseous phase are expected.…”
Section: Fire Retardancysupporting
confidence: 61%
“…57,58 The fire retardancy was tested using a Standard International Group (HK) cone calorimeter. According to ISO 5660, samples with dimensions of 100 Â 100 mm 2 were subjected to 50 kW m À2 ignition for 700 s. 59,60 3. Results and discussion…”
Section: Characterizationmentioning
confidence: 99%
“…The av-EHC values of flameretarding UP composites were reduced by more than 20% compared with those of neat UP, which clearly indicated insufficient combustion in the gaseous phase. 38,39 DMMP possesses effective quenching in the gaseous phase but also increases the amount of smoke, as discussed. However, it is worth noting that the smoke emission of UP/NF3@SiO 2 -D decreased.…”
Section: Flame Retardancy and Smoke Suppression Analysis 331 Loi And ...mentioning
confidence: 92%